Risk Factors for Cervical Cancer: Results from a Hospital-Based Case-Control Study - Reis, Nesrin; Beji, Nezihe K.; KILIÇ, Dilek (My University, 2011)
The aim of this study was to investigate risk factors for cervical cancer in Turkish women. In a hospital-based case-control study in Istanbul, 209 patients with histologically confirmed cervical cancer were compared with 1050 controls, who were admitted to the different departments of the same hospital. Odds ratios (OR) and 95% confidence intervals (Cl) were obtained from multivariate logistic regression analysis, fitted by the method of maximum likelihood.
Keywords: Cervical Cancer